Advances in biological and medical physics. - Lawrence, John H. (John Hundale), 1904-1991; Tobias, Cornelius A. (Academic Press, 1957)
Advances in Biological and Medical Physics, Volume V, provides an overview of the state of knowledge in biological and medical physics. The book opens with a discussion of electron spin resonance and nuclear magnetic resonance and their applications to biology. This is followed by separate chapters on action spectroscopy, the genetics of somatic mammalian cells, partial-cell irradiation, electrical properties of tissue and cell suspensions, quantum effects in human vision, and television techniques in biology and medicine. Subsequent chapters deal with studies on the use of antibodies as carri.